Sex differences in off-target binding using tau positron emission tomography - Ruben Smith; Olof Strandberg; Antoine Leuzy; Tobey J. Betthauser; Sterling C. Johnson; Joana B. Pereira; Oskar Hansson (NeuroImage: Clinical, 2021)
Purpose: Off-target binding in the skull and meninges is observed in some subjects undergoing tau positron emission tomography (PET) and could potentially differ between men and women. In this study we elucidate sex differences in tau off-target binding using three different tau PET tracers. Methods: 541 cognitively unimpaired amyloid-β negative participants underwent tau PET using [18F]flortaucipir (n = 165), [18F]RO948 (n = 189) and [18F]MK6240 (n = 187). Baseline SUVR-values were compared between females and males at the voxel level and using a region-of-interest (ROI) encompassing the skull/meninges. In addition, we assessed the cross-sectional relationship between baseline skull/meninges SUVR and age and assessed change in skull/meningeal SUVR values over time in a subsample with longitudinal data (n = 63). Results: Voxel-wise analysis showed higher meningeal off-target binding in women compared to men across all three tracers. The SUVRs in the skull/meningeal ROI were highest using [18F]RO948, followed by [18F]MK6240 and [18F]flortaucipir (p < 0.001). For all tracers, females showed higher skull/meningeal ROI retention (mean SUVR ± SD [18F]flortaucipir: 0.82 ± 0.14; [18F]RO948: 1.26 ± 0.30; [18F]MK6240: 1.09 ± 0.19) compared to men ([18F]flortaucipir: 0.70 ± 0.11; [18F]RO948: 1.10 ± 0.24; [18F]MK6240: 0.97 ± 0.17) (p < 0.001). For [18F]flortaucipir and [18F]RO948, off-target binding in the skull/meninges decreased with age. Conclusion: There is an effect of sex on off-target retention in the meninges/skull across [18F]flortaucipir, [18F]RO948, and [18F]MK6240 tau PET tracers.